Outlining and tracing of faults in Gazanbulaq— Ziyadkhan area by attribute analysis of 3D seismic survey data - M. Aghayeva (Геофизический журнал, 2020)
The paper is devoted to more detailed study of geological setting of Gazanbulaq, Ziyadkhan and North Ziyadkhan structures by 3D seismic survey data, attribute analysis in particular. At the same time, this study aims to establish more efficient attributes for outlining and tracing of disjunctive dislocations within the limits of Yevlakh-Agjhabedi trough of Middle Kur depression of Azerbaijan. The paper describes the general data on Gazanbulaq field, which is one of the oldest non-anticline fields of Azerbaijan. The history of geological and geophysical studies covering the field is also considered. Despite that the field has been repeatedly studied by use of various techniques some aspects of geological setting have not been studied and therefore the area has been covered by 3D seismic survey in 2014. The results acquired by processing of all data of 3D cube, as well as calculated seismic attributes are described. All attributes are calculated by migrated cube of 3D seismic survey data. All calculated attribute cubes have been analyzed and more detailed knowledge of disjunctive setting of the field has been derived. The most efficient attributes have been defined. Comparison of traditional vertical time slices (sections) of 3D seismic survey cube with calculated sections of Sweetness, RMS Amplitude, Envelope and Ant tracking along the same lines displayed that seismic reflections and peculiarities of setting identified in traditional sections are fully reflected in attribute sections. Faults of small amplitudes identified and hardly traced in traditional time sections are well reflected in sections of all attributes by characteristic complication of wave pattern with chaotic form of attribute amplitudes distribution. The similar image is observed in all maps of calculated attributes for the surface of horizons Gazanbulaq I and II: presence of faults outlined and traced in maps drawn previously for these horizons have been confirmed. Small amplitude faults were outlined and traced in the flank portions of the structures and marked on the structural maps.